Effect of Marine Microalga Chlorella pyrenoidosa Ethanol Extract on Lipid Metabolism and Gut Microbiota Composition in High-Fat Diet-Fed Rats - Wan, Xuzhi (Mar Drugs, 2018)
Effects of marine microalga Chlorella pyrenoidosa 55% ethanol extract (CPE55) on lipid metabolism, gut microbiota and regulation mechanism in high fat diet-fed induced hyperlipidaemia rats were investigated. Structure characterizations of major compounds in CPE55 were determined by ultra-performance liquid chromatography-quadrupole/time of flight mass spectrometry (UPLC-Q-TOF-MS/MS). The compositions of gut microbiota in rats were analyzed by high-throughput next-generation 16S rRNA gene sequencing. Oral administration with CPE55 markedly alleviated dyslipidemia through improving adverse blood lipid profile and inhibiting hepatic lipid accumulation and steatosis. CPE55 has downregulated the gene expression levels of acetyl CoA carboxylase, sterol regulatory element-binding transcription factor-1c, and 3-hydroxy-3-methyl glutaryl coenzyme A reductase and upregulated adenosine 5′-monophosphate-activated protein kinase-α. It has also improved the abundance of bacteria Alistipes, Prevotella, Alloprevotella, and Ruminococcus1 and decreased the abundances of Turicibacter and Lachnospira. Turicibacter and Lachnospira were both positive correlations of metabolic phenotypes. The findings above illustrated that CPE55 might be developed as food ingredients to ameliorate lipid metabolic disorders and hyperlipidaemia.